2018
DOI: 10.1038/s41536-018-0054-3
|View full text |Cite
|
Sign up to set email alerts
|

Rehabilitative exercise and spatially patterned nanofibrillar scaffolds enhance vascularization and innervation following volumetric muscle loss

Abstract: Muscle regeneration can be permanently impaired by traumatic injuries, despite the high regenerative capacity of skeletal muscle. Implantation of engineered biomimetic scaffolds to the site of muscle ablation may serve as an attractive off-the-shelf therapeutic approach. The objective of the study was to histologically assess the therapeutic benefit of a three-dimensional spatially patterned collagen scaffold, in conjunction with rehabilitative exercise, for treatment of volumetric muscle loss. To mimic the ph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(61 citation statements)
references
References 38 publications
4
56
0
Order By: Relevance
“…Aligned nanofiber scaffolds are the preferred biomaterial for muscle reconstruction since they not only promote myofibers alignment but can also be stacked to provide bulk to the engineered tissue. Aligned nanofiber scaffolds have been shown to facilitate NMJ formation in vitro as well as promote alignment of regenerating myofibers in vivo as compared to randomly oriented nanofibers 19,27,37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aligned nanofiber scaffolds are the preferred biomaterial for muscle reconstruction since they not only promote myofibers alignment but can also be stacked to provide bulk to the engineered tissue. Aligned nanofiber scaffolds have been shown to facilitate NMJ formation in vitro as well as promote alignment of regenerating myofibers in vivo as compared to randomly oriented nanofibers 19,27,37 .…”
Section: Discussionmentioning
confidence: 99%
“…Most tissue engineering strategies towards VML repair are evaluated in small animal models 44 . Cell based approaches generally comprise of cell lines (mouse/human) or primary cells and hence are carried out in athymic animals to allow in vivo survival and maturation of the constructs 19,27,44,45 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alarmingly, a recent systematic review, meta-analysis, and network meta-analysis of VML injury studies that included quantitative functional analyses [98] determined that in animal models, rehabilitation approaches for VML injury resulted in worse functional outcomes than if the injury was left to its natural sequela. This work specifically focused on studies testing rehabilitation in animal models in the form of voluntary wheel running, chronic-intermittent electrical nerve stimulation and/or passive range of motion exercises resulting in only modest functional improvements [84,[99][100][101][102][103]. Collectively, these limited clinical and pre-clinical studies indicate that the remaining muscle does not fully recover strength, may be resistant to rehabilitation, and results in long-term disability.…”
Section: Tissue Level Resistance To Physical Therapy In Vml Injurymentioning
confidence: 99%
“…Nakayama et al demonstrate the ability of a three-dimensional nanofibrillar scaffold in combination with an exercise protocol to restore tissue structure and composition in a murine model of volumetric muscle loss (VML). 2 In designing the construct, careful attention was taken to design the scaffold in a way that both is biocompatible and closely mimics the architecture and mechanical properties of native skeletal muscle. Despite the biomimetic nature of the construct, the investigators found that implantation of the scaffold alone yielded no benefit in vascularity or muscle regeneration.…”
mentioning
confidence: 99%